Corn Drying with Zeolite in The Fluidized Bed Dryer under Medium Temperature - Mohamad Djaeni; Nurul Aishah Aishah; Harum Nissaulfasha; Luqman Buchori (IPTEK The Journal for Technology and Science, 2013)
Drying is an important step to find high quality of corn. Based on Standard of National Industry, populer as SNI, number 01-3920-1995, the corn was well stored at moisture content 14% or below (wet basis). However, conventional corn drying dealed with in-efficient energy process and corn quality degradation. This research evaluated the performance of corn drying assisted by zeolite as moisture adsorbent. In this process, the zeolite and corn were placed in the dryer fluidized by warm air as drying medium under 40 - 50oC. The air evaporated water product from corn, and at same time the zeolite adsorbed moisture in air. So, the relative humidity of air in dryer can be kept low in which enhanced the driving force for drying. Beside that, the moisture adsoprtion by zeolite was exothermic process that can supply the energy for drying or keep the dryer temperature. Thus, the drying rate can be faster. This work foccussed to observe the effect of drying temperature, air velocity, and corn to zeolite ratio on drying time as well as corn quality. As indicators, the drying rate was estimated and the proxymates content such as protein, fat, and carbohydrate content were analyzed. The results showed that compared with conventional fluidised bed dryer, corn drying with zeolite, can speed up drying time as well as improving the constant of drying rate. In addition, the corn proximate nutrition content can be well retained. At operating temperature 40oC, air velocity 9 m.s-1, and zeolite to corn ratio 1:2, the drying time can be 60 minutes shorter compared to that without zeolite.